ANALISIS BRAND EQUITY TERHADAP CUSTOMER LOYALTYPADA SPBU DI JAKARTA - Imam Arif Fikri (2023)
This research is quantitative study that aims to compare brand equity, and customer loyalty in Pertamina companies in the Jakarta area. This research used 100 respondents as a sample with purposive sampling method. The analysis technique in this study uses the SmartPLS. The results of this study indicate that :(1) brand awareness Pertamina has no effect on customer loyalty (2) brand association Pertamina has an effect on customer loyalty (3) perceived quality Pertamina has no effect on customer loyalty (4) brand loyalty Pertamina has an effect on customer loyalty.